TISSUE INTEGRATION AND CELLULAR RESPONSE TO COLLAGEN BIOSTIMULATORS IN OROFACIAL HARMONIZATION: AN INTEGRATIVE REVIEW - Nascimento, Marvin; Barbosa, Carlos Henrique da Luz; Farzat, Thays de Almeida Marinho; Vieira, Patrick de Lima; Silva, Caroline Grijó; Almeida , Aline Raybolt dos Santos (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: Collagen biostimulators are fundamental biomedical devices in orofacial harmonization, recognized for their ability to induce biological activity that promotes tissue regeneration and improves skin quality. Among the most commonly used biostimulators are Poly-L-lactic Acid (PLLA), Calcium Hydroxyapatite (CaHA), and Polycaprolactone (PCL). These materials exhibit characteristics of biocompatibility, biodegradability, and biofunctionality, enabling cell proliferation and collagen production, processes that drive neocollagenesis and neoelastogenesis. Review Question: What is the impact of collagen biostimulators on tissue integration, healing, and foreign body response in humans and animals within the context of facial harmonization and experimental studies? Materials and Methods: This integrative review followed the PCC method, including studies addressing collagen biostimulators, tissue regeneration, repair, healing, and foreign body responses. Exclusion criteria comprised studies that focused on pathologies, systemic health alterations, body harmonization, bone grafts, dermal fillers, botulinum toxin, or those with an exclusively clinical focus. The research sources included PubMed, Google Scholar, SciELO, Virtual Health Library, Dimensions, and BASE. Results: From 246 identified records, 11 studies met the inclusion criteria. PLLA was associated with increased collagen synthesis through M2 macrophage polarization and modulation of the inflammatory response. CaHA demonstrated bioactivity by interacting with tissues to stimulate neocollagenesis and neoelastogenesis. PCL facilitated tissue regeneration by providing scaffold properties and controlled biodegradation, supporting extracellular matrix formation. Final Considerations: These biostimulators exhibited distinct cellular and tissue responses, reflecting their different mechanisms of action. Collagen biostimulators show significant potential to enhance tissue integration and regeneration in orofacial harmonization, although their effects are material-specific.